Creating a Culture of Continuous Improvement in Outpatient Laboratories: Effects on Wait Times, Employee Engagement, and Efficiency. (July 2019) - Featherall, Joseph; Chaitoff, Alexander; Simonetti, Anthony; Bena, James; Kubiak, Daniel; Rothberg, Michael; Roumina, Kavous; Hurle, Nathan; Henricks, Walter; Yerian, Lisa
Transforming health care remains a challenge as many continuous improvement (CI) initiatives fail or are not sustained. Although the literature suggests the importance of culture, few studies provide evidence of cultural change creating sustained CI. This improvement initiative focused on creating cultural change through goal alignment, visual management, and empowering frontline employees. Data included 113 133 encounters. Cochran-Armitage tests and X-bar charting compared wait times during the CI initiative. Odds of waiting <15 minutes increased in both phase 2 (odds ratio = 3.57, 95% confidence interval = [3.43-3.71]) and phase 3 (odds ratio = 5.39, 95% confidence interval = [5.07, 5.74]). At 3 years follow-up, 95% of wait times were <15 minutes. Productivity increased from 519 to 644 patients/full-time equivalent/month; 33/42 Press Ganey employee engagement components significantly improved. This study demonstrates the efficacy of a culture of CI approach to sustain wait time improvement in outpatient laboratory services, and should be considered for application in other areas of health care quality.